Factors Influencing Teachers’ Self-Efficacy in Virtual Classrooms - Abeer Althaqafi; Ibtissam Alqahtani (Studies in Learning and Teaching, 2026)
The sudden transition to online teaching due to the Covid-19 pandemic has compelled teachers to use a new mode of teaching, which is online teaching, whether or not they are competent users of online tools. Therefore, this study aims to explore Saudi female EFL teachers’ perceptions of factors that might influence their self-efficacy in online teaching. Drawing on self-efficacy theoretical framework, the study measured efficacy beliefs through external and internal barriers to technology integration. Following a quantitative research design, the study utilized a questionnaire to investigate teachers’ perceptions of external and internal factors influencing their self-efficacy in online teaching. The questionnaire was administered and completed by 60 female Saudi teachers. The results indicated that internal barriers, such as knowledge, skills, beliefs and attitudes, affect teachers’ SE more negatively than external ones, such as time, technical support and PDs. In addition, it has been found that novice teachers perceived online teaching more positively than experienced ones. However, the study revealed that both experienced and novice teachers required support and assistance, particularly in the online pedagogy knowledge base. The study calls for reform in teacher preparation programs and calls for the need to provide a pedagogically-oriented online curriculum.